Awkward working postures and precision performance as an example of the relationship between ergonomics and production quality - Ngcamu, Nokubonga Slindele (Sma) (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2009)
Ergonomics aims to improve worker health and enhance productivity and quality. Knowledge and practical evidence of this relationship would be instrumental for optimising organisational performance particularly in industrially developing countries where the discipline is still in its developmental stages. Therefore this thesis set out to analyse the relationship between ergonomics deficiencies and performance. A survey was first conducted to establish the severity of quality problems in the South African manufacturing industry and to determine if these were related to Ergonomic deficiencies. The results indicated that quality problems continue to plague industry, a challenge associated with huge cost implications. Furthermore organisations were not cognisant of the fact that ergonomics deficiencies such as poor workstation design and awkward or constrained working postures are a major contributing factor to poor quality and performance decrements. This demonstrates that much is yet to be done in raising awareness about the benefits of ergonomics in South Africa and other industrially developing countries. However, for this to be effective, tangible evidence of these purported benefits is required. In lieu of this, a laboratory study was then conducted to establish the relationship between awkward working postures and the performance of precision tasks. Acknowledging that the task and the worker are interrelated elements, the impact of precision task demands on the postural strain experienced by the human was also investigated. A high and low precision task quantified positional precision while a force task (combination of pushing and pulling) was utilised to assess the ability to maintain a precise force over time. These three tasks were performed in eight different postures; namely seated, standing, stooping 300 and 600, working overhead, lying supine, and twisting to either side. A combination of the tasks and postures resulted in 24 experimental conditions that were tested on forty eight healthy male and female participants. The performance related dependent variables were movement time, deviation from the centre of the target, and the trend/slope followed by the force exerted. Muscle activity of eight arm, shoulder and back muscles, iii supplemented with heart rate and local ratings of perceived exertion, were utilised to quantify the impact of the tasks and the postures on the individual. The results revealed that awkward working postures do in fact influence performance outcomes. In this regard, awkward working postures (such as overhead work and lying supine and stooping) were evidenced to significantly affect movement time, deviations from the target and the ability to maintain a constant force over time. These variables have a direct relationship with organisational priorities such as productivity and quality. Furthermore, the results indicated that high precision demands augment postural strain elicited through high muscle activity responses and may have negative implications for the precipitation of musculoskeletal disorders. Essentially, the work done on this thesis reflected the complex nature of ergonomics by drawing on both macro and micro-ergonomics approaches. In so doing, challenges perceived to be relevant to industry as reported by organisations formed the foundation for further laboratory studies. Therefore, more collaborative research and knowledge transfer between industry and ergonomics researchers is a necessity particularly in industrially developing countries where ergonomics is still in its developmental stages.
Keywords: Human engineering; Posture; Posture disorders; Musculoskeletal system -- Diseases; Work -- Physiological aspects